Developmental revolution : North Africa, Middle East, South Asia - Polk, William Roe.; The Middle East Institute (Washington, D.C. : Middle East Institute, 1963)
This book consists of papers presented at the Middle East Institute, May 1963. The papers examine the concerns, theories and information that participants in the developmental revolution in North Africa, Middle East and South Asia.
Modification of papers read at the 17th annual conference held by the Middle East Institute.
Includes bibliographical references.
lje 18/04/2018
Loans
Keywords: Economic development; Economic assistance, American; Developing countries